Effects of Transdermal and Oral Oestrogen Replacement Therapy on C-Reactive Protein Levels in Postmenopausal Women: A Randomised, Placebo-Controlled Trial - Post, M. S.; van der Mooren, M. J.; Stehouwer, C. D. A.; van Baal, W. M.; Mijatovic, V.; Schalkwijk, C. G.; Kenemans, P. (Thrombosis and Haemostasis, 2002)
To investigate the effect of postmenopausal oral and transdermal hormone therapy on plasma levels of C-reactive protein (CRP), we performed a randomised, double-blind, double-dummy, placebo-controlled, 15-month study. One hundred and fifty-two healthy hysterectomised postmenopausal women received daily either placebo (n = 49), or transdermal 17 β-oestradiol (E2) 50 µg (tE2 group, n = 33), or oral E2 1 mg (oE2 group, n = 37), or oral E2 1 mg combined with gestodene 25 µg (oE2 + G group, n = 33) for thirteen 28-day treatment cycles, followed by four cycles placebo for each group. Data were collected at baseline and in cycles 4, 13 and 17. In cycle 13, CRP was significantly increased in the oE2 group compared to placebo (P = 0.004). The median percentage change from baseline versus placebo was +75% (P <0.001). In cycle 17, significantly lower values were observed in the oE2 group compared to cycle 13 and to the placebo group (-49%, P <0.001). There were no significant changes versus placebo in the other groups. In conclusion, oral E2 significantly increased CRP levels. This change was larger than the increase found during oral E2 + G. Transdermal E2 did not affect CRP levels.
Keywords: C-reactive protein; postmenopausal; hormone replacement therapy; oestrogen; gestodene